TAN MALAKA: FILSAFAT REALISME KETIMURAN - salahuddin harahap (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2020)
Tan Malaka, is one of the Indonesian thinkers who seems to have quite a high concern for philosophy as stated in his fairly popular work MADILOG stands for "Materialism-Dialectics and Logic". A great work put the foundations of philosophy and logic which, if developed, is believed to give birth to a new philosophical model and not just a transfer of the philosophy of Western Materialism, Dialectic Socialism and Aristotelian Formal Logic. The author prefers to call "Philosophy of Eastern Realism" towards the philosophy developed by Tan Malaka with the following considerations: First, in general the territory of Indonesia is included in the category of agrarian (close to nature) so that the nature of thought is very laden with mysticism or myth, so that necessary encouragement more realistic and logical so it is called "Realism". Second, the term eastern represents typical traditions, culture, religion and territory so as to necessitate a strong acculturation process for any ideas, thoughts and traditions that originate from outside. At least these two considerations have been exposed in various writings by Tan Malaka, which the writer believes can be formulated as a new form of philosophy specifically for the treasures of Eastern Philosophy in particular Indonesia.Keywords: Tan Malaka, Eastern Realism Philosophy.